Characteristics study for a hybrid power supply system - Hu, Fangjie (2014)
The increasing popularity of electrical vehicle (EV) has, undoubtedly, being witnessed these decades. Due to the feature of zero emission, EV technology keeps standing forefront in the discussion of reducing global carbon dioxide emission. Nevertheless, two major bottlenecks, including the lifetime and the charging rate of the battery, have restricted its application range towards EV. In this research, the hybrid power supply system (HPSS), comprising battery (BA) and supercapacitor (SC), is proposed to prolong the operational life-span and reduce charging time of BA. Based on the previous works mentioned in the literature review, SC is capable of large current injection and high power density which are superior to BA. Therefore, BA and SC have complementary characteristics that the combination would attain the best of each. This research analyses both advantages and disadvantage for each pre-existing HPSS configurations, and proposes a new circuit topology as well as the corresponding control strategy designed for fast charging. The simulation result indicated the charging time could be reduced from 100 minutes to 54.8 minutes by implementing this design.